Unbiased Characterization of the Microbiome and Virome of Questing Ticks - Chandra, Shona; Harvey, Erin; Emery, David; Holmes, Edward C.; Šlapeta, Jan (Frontiers in Microbiology, 2021)
Due to their vector capacity, ticks are ectoparasites of medical and veterinary significance. Modern sequencing tools have facilitated tick-associated microbiota studies, but these have largely focused on bacterial pathogens and symbionts. By combining 16S rRNA gene sequencing with total RNA-sequencing methods, we aimed to determine the complete microbiome and virome of questing, female Ixodes holocyclus recovered from coastal, north-eastern New South Wales (NSW), Australia. We present, for the first time, a robust and unbiased method for the identification of novel microbes in ticks that enabled us to identify bacteria, viruses, fungi and eukaryotic pathogens. The dominant bacterial endosymbionts were Candidatus Midichloria sp. Ixholo1 and Candidatus Midichloria sp. Ixholo2. Candidatus Neoehrlichia australis and Candidatus Neoehrlichia arcana were also recovered, confirming that these bacteria encompass I. holocyclus’ core microbiota. In addition, seven virus species were detected—four previously identified in I. holocyclus and three novel species. Notably, one of the four previously identified virus species has pathogenic potential based on its phylogenetic relationship to other tick-associated pathogens. No known pathogenic eukaryotes or fungi were identified. This study has revealed the microbiome and virome of female I. holocyclus from the environment in north-eastern NSW. We propose that future tick microbiome and virome studies utilize equivalent methods to provide an improved representation of the microbial diversity in ticks globally.